The Origin of The Emergence of Arabic Lexicology And Its Characters / Cikal Bakal Munculnya Leksikologi Arab dan Para Tokoh-Tokohnya - Balkis Aminallah Nurul Mivtakh (UIN Raden Mas Said Surakarta, 2022)
This article aims to examine the history of Arabic lexicology in the classical era and the figures who contributed to the field of Arabic lexicology. There are three questions that will be answered through this research, namely First,